(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The article discusses and analyzes various types of sedimentation tanks, studies the dynamics of sediment changes and their deposition location in the supply section of the CMC. The paper presents the results of field studies. Recommendations are given to establish the location of the sump in the channel of the supply channel. And also on the basis of full-scale data, the design parameters of the sump are proposed, which allow to improve the operating conditions of the supply channels of pumping stations.